HUBUNGAN PERSEPSI WANITA USIA SUBUR TENTANG EFEK SAMPING INTRAUTERINE DEVICE (IUD) DENGAN MOTIVASI DALAM PEMILIHANNYA SEBAGAI ALAT KONTRASEPSI - Valentina, Dewa Ayu Putu Pebri; Suindri, Ni Nyoman; Darmapatni, Made Widhi Gunapria (Maternity and Neonatal : Jurnal Kebidanan, 2025)
One of the factors contributing to the Maternal Mortality Rate (MMR) in Indonesia is the still high rate of unwanted pregnancies. Encouraging the use of long-term contraceptive methods (MKJP) including intrauterine contraceptive devices (IUDs) is one strategy to reduce MMR. IUDs are still less popular, due to negative opinions about their side effects. This factor was taken into account to determine the relationship between the motivation of women of childbearing age (WUS) to choose IUDs as their contraceptives. A total of 46 WUS were selected for this study using purposive sampling and a correlational analysis approach. The research instrument was a Likert scale questionnaire, and the Spearman correlation test was used to analyze the relationship between the two variables. The median score for motivation was 56.00, and the median score for perception was 57.00. The Spearman correlation statistical test showed a significant relationship between motivation and perception (p = 0.000), with a correlation coefficient of 0.675, so the relationship is categorized as strong. It can be concluded that the more positive the WUS perception of the negative consequences of IUDs, the more motivated they are to use IUDs as a contraceptive method. Creating a positive perception can increase motivation to use IUDs, so this study recommends increasing education and counseling on long-term contraceptive methods (LMC).